An Investigation on Body Condition Score, Body Weight, Calf Weight and Hematological Profile in Crossbred Dairy Cows Suffering from Dystocia - Yildiz, Hamit; Saat, Nevzat; Simsek, Halil (Univ Agriculture, Fac Veterinary Science, 2011)
The knowledge of hematological values is useful in diagnosing various pathological and metabolic disorders, which can adversely affect reproductive performance of cows. The aim of this study was to investigate body condition score (BCS), body weight, calf weight, blood erythrocyte parameters and total and differential leukocyte count changes in dystocia-affected crossbred dairy cows. Values of mean corpuscular volume (MCV) and neutrophil count were markedly increased (P<0.001) in the dystocia group compared to normal calving group. The levels of mean corpuscular haemoglobin concentration (MCHC) and hematocrit in dystocia-affected cows were significantly lower (P<0.001) than normal control group. However, in cow suffering from dystocia, counts of the white blood cells (WBC), red blood cells (RBC), haemoglobin concentration, mean corpuscular haemoglobin (MCH), eosinophils, basophils, lymphocytes and monocytes were not different from the normal parturient group. In cows with dystocia, BCS, age and parity of dams did not show significant difference compared to normal parturition. However, body weight in cows with difficult calving was lower (P<0.05) than spontaneous calving cows. These results suggest that hematocrit, MCV, MCHC and neutrophil counts were significantly affected due to dystocia in cattle. BCS, age and parity of the cow had no affect on the occurrence of dystocia. (C) 2011 PVJ. All rights reserved
Keywords: Body condition score; Calf weight; Crossbred Cattle; Dystocia; Hematological profile